Prevalence of Trypanosoma cruzi's Discrete Typing Units in a cohort of Latin American migrants in Spain (2016)
Chagas disease is caused by the protozoan Trypanosoma cruzi. This is an endemic disease in the Americas, but increased migration to Europe has made it emerge in countries where it was previously unknown, being Spain the second non endemic country in number of patients. T. cruzi is a parasite with a wide genetic diversity, which has been grouped by consensus into 6 Discrete Typing Units (DTUs) affecting humans. Some authors have linked these DTUs either to a specific epidemiological context or to the different clinical presentations. Our main objective was to describe the T. cruzi DTUs identified from a population of chronically infected Latin American migrants attending a reference clinic in Madrid. 149 patients meeting this condition were selected for the study. Molecular characterization was performed by an algorithm that combines PCR of the intergenic region of the mini exon-gene, the 24S? and 18S regions of rDNA and the variable region of the satellite DNA. A descriptive analysis was performed and associations between geographical/clinical data and the different DTUs were tested. DTUs could be determined in 105 out of 149 patients, 93.3% were from Bolivia, 67.7% were women and median age was 35 years (IQR 29-44). The most common DTU found was TcV (58; 55.2%), followed by TcIV (17; 16.2%), TcII (10; 9.5%) and TcI (4; 3.8%). TcIII and TcVI were not identified from any patient, and 15.2% patients presented mixed infections. In addition, we determined DTUs after treatment in a subset of patients. In 57% patients had different DTUs before and after treatment. DTUs distribution from this study indicates active transmission of T. cruzi is occurring in Bolivia, in both domestic and sylvatic cycles. TcIV was confirmed as a cause of chronic human disease. The current results indicate no correlation between DTU and any specific clinical presentation associated with Chagas disease, nor with geographical origin. Treatment with benznidazole does not always clear T. cruzi's genetic material from blood, and DTUs detected in the same patient may vary over time indicating that polyparasitism is frequent. © 2016 Elsevier B.V.